Causes of post-caesarean surgical site infection at South Konawe Hospital, Southeast Sulawesi, Indonesia, February - July 2017 - Mokhamad Anhar Dani; Rizki Pranadyan; Muhammad Yusuf; Budi Prasetyo (Majalah Obstetri dan Ginekologi, 2018)
Objectives: To analyze the causes of post-caesarean section surgical site infection (SSI) at South Konawe Hospital, Southeast Sulawesi, Indonesia, between February and July 2017.Materials and Methods: Retrospective study using descriptive method with cross-sectional design from February to July 2017 in inpatient and outpatient wards at Obstetrics and Gynecology Outpatient Clinic, South Konawe Hospital. The population was the patients medical records.Results: There were nine cases (7.75%) from totally of 116 cases of caesarean section with SSI. Based on SSI type, there were four cases (44.4%) with superficial SSI and 5 cases (55.5%) with deeper classification of SSI. SSI was dominated by women of productive age with age 20-35 years in 66.6% case. The lowest BMI was 22 kg/m2 and the highest BMI was 41.5 kg/m2. Hemoglobin levels were higher than 11 g/dL (66.6%). The most surgical action to be performed was emergency operation in 8 cases (15.09%).Conclusion:Causal characteristics of SSI at South Konawe were age of 20-35 years, the lowest BMI of 22 kg/m2 and the highest BMI 41.5 kg/m2, hemoglobin levels higher than 11 g/dL, and the need of emergency operation.